Outcomes of transvers pinning versus antegrade intramedullary elastic nail in surgical fixation of 5th metacarpal neck fractures - A Ibrahim, Mohamed Adel; kornah, Bahaa A.; Akl, Mohamed Nasr; Abdelkader, Mohamed G; Abulsoud, Mohamed I.; Shwitter, Lotfy Mohamed; Ismail, Mohamed A.I.; Elgahel, Mostafa M. (Acta Biomedica Atenei Parmensis, 2026)
Background: The most prevalent hand fracture is a fifth metacarpal neck fracture. Due to hand impairments caused by improper therapy for fifth metacarpal neck fractures, there is a negative economic impact due to disabilities in workers', athletes', and housewives' hands. Additionally, there are aesthetic side effects and deficits in metacarpophalangeal extension.Objective: Our study aimed to evaluate and juxtapose clinical and radiological outcomes following the use of percutaneous transverse k-wire versus antegrade intramedullary elastic nail for the treatment of fifth metacarpal neck fractures.Patients and Methods: A prospective comparative study involving 40 patients presenting with 5th metacarpal neck fractures, who were treated surgically participated. Two patient groups were formed: Group 1 (20 patients) received fixation by single ante-grade intramedullary elastic nail. Group 2 (20 patients) were treated with fixation by percutaneous transverse k-wire. Both groups followed up for a full year.Results: All patients recovered to their pre-injury activity level at the last follow-up, had excellent functional and acceptable results, and had achieved bony union. There were no significant postoperative or intraoperative complications noted, and there was no statistically significant difference between the two groups in terms of complications, pain, hand grip strength, or time of union. The total active motion (TAM) score demonstrated significant improvement in both groups with slight increase in significance in the intramedullary elastic nail group.Conclusion: Based on the outcomes, high patient satisfaction and low complication rates both methods are considered valid options for safe, reliable and effective surgical management for 5th metacarpal neck fractures.